Keep an eye on the crime – a new look at the forensic use of post-mortem eye examination to estimate time of death (Journal of Medical Science, 2023)
Determining the time of death plays a crucial role in a forensic post-mortem examination. Many methods for the time of death (TOD) determination have been developed. However, most are not applicable during the first hours after death and produce large post-mortem interval (PMI) ranges. Eye examination makes it possible to precisely determine the time of death during the initial period after death with half-hour accuracy.. In recent years methods for estimating the time of death by measuring the changes in the eye have made great strides. Those methods use the changes in the reaction to drugs and macroscopically visible morphological changes. Experimental studies also produced equations that can estimate the post-mortem interval using biochemical, electrochemical and thermal changes within the eye.